Gerakan Sd Negeri Bone Hidup Sehat Bebas Diare Di Desa Bone Kecamatan Nekamese Tahun 2024 - Novian A Yudhaswara; Agnes Rantesalu; Ni Ketut Yulianasari; Aldiana Astuti; Marni Tangkelangi (STIKES Columbia Asia Medan, 2025)
Cleanliness of the school environment, health of the student environment in the teaching and learning process, based on the analysis of the situation above, especially the location of the school partner and conversations with the principal and teaching staff. This activity began with an interview, it was found that students did not have maximum knowledge about health, especially diarrhea, as evidenced by the pre-test interview 70% answered correctly.The expected output of this program is the awareness of school administrators, students about clean living patterns that must be applied in the school environment in order to create student welfare. So that in the long term, a clean living pattern has been embedded in all school children and from there it is hoped that it can create a school environment, especially school children who are prosperous and free from disease. In the socialization, the Team also demonstrated the implementation of a clean living pattern in the school environment such as washing hands with soap and cleaning up trash properly by SDN Bone students. At the end of the activity, a post-test was carried out with the same questions randomly, 90% of the answers were correct, the school hopes that this educational movement can increase the knowledge of teachers and students as an effort to improve student health and prevent diarrhea.